2016
DOI: 10.1007/s12070-016-0989-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type 1 Tympanoplasty on the Quality of Life of CSOM Patients

Abstract: Chronic suppurative otitis media (CSOM) continues to be an important public health problem despite significant advances in medical science. Ear discharge, pain, discomfort, difficulty in hearing, limitation of routine activities and emotional problems due to CSOM cause a significant impact on the health and general well being of the patient. We have done Type 1 tympanoplasty in tubotympanic type of COM to reconstruct the tympanic membrane and alleviate the symptoms of the patients. This study presents an analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…19 In Satyawati et al study the success rate regarding perforation closure was 91.5%, Bhatia et al showed 82% graft uptake, Yadav et al accounting for an 80% success rate. 20,21 In Anoop et al study, in the endoscopic group, there was 90% uptake of graft and in microscopic group it was 85%. 17 In Thirumaran et al study, the graft uptake rate was 93.3% in the endoscopic group, whereas it was 90% in the microscopic group.…”
Section: Discussionmentioning
confidence: 94%
“…19 In Satyawati et al study the success rate regarding perforation closure was 91.5%, Bhatia et al showed 82% graft uptake, Yadav et al accounting for an 80% success rate. 20,21 In Anoop et al study, in the endoscopic group, there was 90% uptake of graft and in microscopic group it was 85%. 17 In Thirumaran et al study, the graft uptake rate was 93.3% in the endoscopic group, whereas it was 90% in the microscopic group.…”
Section: Discussionmentioning
confidence: 94%
“…Batni et al documented 88% success rate of type I tympanoplasty, Bhatia et al claimed it to be 82%, for Onal et al it was 71%. 8,10,11 Callioglu et al reported 89.5% successful graft uptake in their study. 12 The rate of surgical success-integration of the graft -was 93.3% as stated by Naderpour et al 6 Kamath et al documented successful uptake of graft post type I tympanoplasty to be 80%.…”
Section: Discussionmentioning
confidence: 76%
“…We assessed 221 full texts for eligibility as 18 were not able to be retrieved, of which we excluded 188 references. We included 33 studies (8–40) in the systematic review with full details available in a separate table [Supplementary Content 3, http://links.lww.com/MAO/B681], of which seven studies with similar study design (7–13) were included for the meta-analysis. A flowchart of the number of articles included or excluded at each stage is available in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies (60.6%) were undertaken in India, three studies (9.1%) in China, two studies (6.1%) each in Thailand and Bangladesh, and one study (3.0%) each in Korea, Nepal, Iraq, Italy, Egypt, and Pakistan. In terms of study design, 13 studies (11,19,20,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) were randomized and 20 (7)(8)(9)(10)12,13,18,21,22,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) were nonrandomized. The inclusion and exclusion criteria of all studies are summarized in Supplementary Content 3, http://links.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation